Art Summer '96 : 46 Estonian Artists : graphic art, painting, sculpture, installation. - Peil, Mirjam (Tallinn : Tallinna Raamatutrükikoda, 1996)
Eelma, Sirje ; Kalm, Anu ; Kask, Eve ; Keerend, Avo ; Kurema, Kadi ; Liiva, Silvi ; Meel, Raul ; Neidre, Naima ; Nukke, Mall ; Smagar, Piret ; Tolli, Vive ; Viik, Urmas ; Vint, Mare ; Vasserman, Benjamin ; Üksine, Marje ; Allik, Paul ; Allsalu, Vano ; Arrak, Jüri ; Lapin, Leonhard ; Ole, Kaido ; Parmasto, Anne ; Pere, Peeter ; Pääsuke, Tiit ; Tolts, Andres ; Vinogradov, Valeri ; Vint, Toomas ; Kelpman, Rein ; Mildeberg, Jüri ; Someri, Bruno ; Ulas, Peeter ; Mikk, Toomas ; Mikof, Mare ; Ojaver, Jüri ; Ojaver, Terje ; Palm, Hille ; Palm, Lembit ; Prääts, Rait ; Pärg, Rait ; Seakülzst, Simson ; Seppet, Ahti ; Soans, Jaak ; Starkopf, Hannes ; Vernik, Vergo ; Viies, Edgar ; Väli, Ekke ; Juske, Ants
biog., ind. tent., gr. tent., prijzen per kunstenaar
Engels & Ests
Art Summer '96 : 46 Estonian Artists, Linnagalerii & Endla teater, Pärnu, 16.06.96 - 17.08.96 ; Raegalerii, Kuressaare, 9.06.96 - 24.08.96
boek
Keywords: Estland